2018
DOI: 10.1039/c7ra13375h
|View full text |Cite
|
Sign up to set email alerts
|

A novel crosslinking agent of polymethyl(ketoxime)siloxane for room temperature vulcanized silicone rubbers: synthesis, properties and thermal stability

Abstract: A novel cross-linker polymethyl(ketoxime)siloxane was synthesized and then was cured with hydroxyl-terminated polydimethylsiloxane matrix to fabricate a series of novel RTV silicone rubber. Their properties was comparatively investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 49 publications
(49 reference statements)
0
15
0
Order By: Relevance
“…Then the rubber compounds were kept in a water bath at 70°C for 24 h to provide humidification. In literature, humidification step was found to be essential to obtain silane grafting onto polymer matrix prior to cross‐linking 9,12,16,18 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Then the rubber compounds were kept in a water bath at 70°C for 24 h to provide humidification. In literature, humidification step was found to be essential to obtain silane grafting onto polymer matrix prior to cross‐linking 9,12,16,18 …”
Section: Methodsmentioning
confidence: 99%
“…There are some studies on silane vulcanization met in literature and most of these studies focus on cross‐linking of polyethylene 8,9,12,16–20 . Sirisinha and Meksawat evaluated peroxide and silane cross‐linking systems for ethylene‐octene copolymers in terms of their mechanical properties 8 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of synthesis, cyclic siloxanes are frequently used as precursors for the synthesis of high performance polysiloxane elastomers, 12,13 and as cross-linking agents to strengthen materials. [14][15][16] Recently, polysiloxanes and cyclic siloxanes functionalized with fluorophores have exhibited excellent sensing ability to detect specific chemical species. For example, Ren et al reported tetraphenylethene units modified into polysiloxane chains possessing fluorescence ability and capable of detecting the vapor-phase of explosive compounds.…”
Section: Introductionmentioning
confidence: 99%